Identifikasi Dan Analisa Karakteristik Keterdapatan Sink Hole Di Area Paket Pembangunan Jalan Baru Jerukwudel-Baran-Duwet, Gunung Kidul, DIY - Aloysius Andrianto Saputro; Christanto Yudha Saputra Sukamta; Herlina Sulistyani (Media Ilmiah Teknik Sipil, 2021)
The construction of a new road that crosses the village of Jerukwudel-Baran-Duwet, is one of the development projects aimed at the development of road infrastructure in the South Coast region of Java. The construction of this road is in the area of Gunung Kidul Regency which is has a karst morphology, it causes the formation of sink holes that can trigger the occurrence of soil sinking (luweng) and endanger buildings / construction above or surrounding areas. The research method conducted by the author is the retrieval of field data supported by geoelectric data. From the field, obtained 26 sink holes that are divided into 2 types, collapse sink hole (18 locatiosn) is on the cliff and has an average diameter of 1.1 meters. Then the drop out sink hole (8 locations) is on the body of the road, and has an average diameter of 0.9 meters. The dominant lithology is carbonate rocks (packestone, wackestone and crystalline rock). There are two morphology forms in this area, doline and cone karst, both forms are associated with the type of sink hole formed. Where on the doline found dropout sink hole and in cone karst found collapse sink hole. From the interpretation of geoelectric data, it can also be determined the potential of subsurface cavities and soil sinks that have formed on the surface.